Some aspects of the life history and bionomics of the Fig moth, Ephestia cautella (Wlk.), and some comparisons with the mediterranean flour moth, E. kuhniella (Zell) and the tobacco moth, E. elutella (Hb.) - Newman, Patricia Ann (Department of Biological Sciences, 2016)
Includes bibliographical references (pages 68-73).